Pengaruh Muatan Etika dalam Pendidikan Akuntansi Terhadap Presepsi Etika Mahasiswa - Adinda Tri Widya Wulan Dari; Rita Susanti (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
Students' ethical perceptions are very important in the ethical content of accounting education. Ethics plays a key role in shaping the character and professional behavior of accounting students which will then have a positive impact on accounting practices in the world of work. This understanding aims to find out how ethics in accounting education influences students' ethical perceptions. This research uses a quantitative method with the ethical content variable in accounting education as the variable (X) and students' ethical perceptions as the variable (Y). The results of this research show that the ethical content in accounting education has a significant influence on students' ethical perceptions.